Incidence of Naloxone Redosing in the Age of the New Opioid Epidemic. (2nd November 2017) - Klebacher, Ronald; Harris, Matthew I.; Ariyaprakai, Navin; Tagore, Ammundeep; Robbins, Vince; Dudley, Larissa Sophia; Bauter, Robert; Koneru, Susmith; Hill, Ryan D.; Wasserman, Eric; Shanes, Andrew; Merlin, Mark A.
Abstract: Study Objective : Naloxone, an opioid-antagonist deliverable by an intra-nasal route, has become widely available and utilized by law enforcement officers as well as basic life support (BLS) providers in the prehospital setting. This study aimed to determine the frequency of repeat naloxone dosing in suspected narcotic overdose (OD) patients and identify patient characteristics.Methods : A retrospective chart review of patients over 17 years of age with suspected opioid overdose, treated with an initial intranasal (IN) dose of naloxone and subsequently managed by paramedics, was performed from April 2014 to June 2016. Demographic data was analyzed using descriptive statistics to identify those aspects of the history, physical exam findings. Results:  A sample size of 2166 patients with suspected opioid OD received naloxone from first responders. No patients who achieved GCS 15 after treatment required redosing; 195 (9%) received two doses and 53 patients received three doses of naloxone by advanced life support. Patients were primarily male (75.4%), Caucasian (88.2%), with a mean age of 36.4 years. A total of 76.7% of patients were found in the home, 23.1% had a suspected mixed ingestion, and 27.2% had a previous OD. Two percent of all patients required a third dose of naloxone.Conclusion:   In this prehospital study, we confirmed that intranasal naloxone is effective in reversing suspected opioid toxicity. Nine percent of patients required two or more doses of naloxone to achieve clinical reversal of suspected opioid toxicity. Two percent of patients received a third dose of naloxone.